The association between leisure activity and mental health in the older adults in China: amazing Guangchangwu - Yu, Jiajun; Chiu, Ya-Ling; Guu, Sy-Ming; Wang, Jying-Nan (Frontiers in Public Health, 2024)
Objective: Since the mental health of older adult is an important topic in the aging society, the main purpose of this study is to understand the mental health status of the older adult in China under different conditions. More importantly, although people generally believe that leisure activities can improve mental health, the impact of these activities on older adult has not yet been fully discussed. Hence, this study further explores that what kind of leisure activity is associated with mental health of the older adult given different conditions.We conducted a cross-sectional questionnaire survey to explore the relationships of various leisure activities on mental health among older adults under different demographics. This study used the Geriatric Depression Scale short forms scale (GDS-15) to assess the mental health of older adults. Based on a sample of 2006 participants, both two-sample t-test and ANOVA were adopted to analyze the characteristics of mental health among specific subsamples.Results: Our findings indicated that older adults generally have higher mental health scores if they do not have chronic diseases, live with other family members, or reside in urban. First, three leisure activities including walking, Guangchangwu, and hiking have positive associations on mental health for older adults with chronic diseases. Second, the older adults living alone engaged in Guangchangwu or hiking significantly associated with their good mental health. Finally, only Guangchangwu has a significantly positive associated with the mental health of rural older adults.Conclusions: Based on our results, the government and healthcare planners can better allocate limited resources under different conditions to promote certain leisure activities, which are helpful to enhance the mental health of older adults. Guangchangwu is an activity that meets the characteristics of Chinese culture, so we further conclude that it is significantly associated with the good mental health of older adults in China.